Anti- enterococcus faecalis, cytotoxicity, phytotoxicity, and anticancer studies on Clausena excavata Burum. f. (Rutaceae) leaves - Albaayit, Shaymaa Fadhel Abbas; Maharjan, Rukesh; Abdullah, Rasedee; Mohd Noor, Mohd Hezmee (Hindawi Publishing, 2021)
Background: Clausena excavata Burum. f. has long been applied in ethnomedicine for the treatment of various disorders like rhinitis, headache, cough, wound healing, fever, and detoxification. This study is aimed at investigating the antibacterial activity against Enterococcus faecalis ATCC 49532 using AlamarBlue assay and atomic force microscopy (AFM) as well as the cytotoxicity, anticancer, and phytotoxicity of C. excavata. Method: Bacterial cell viability was performed by using microplate AlamarBlue assay. Atomic force microscopy was used to determine morphological changes in the surface of bacterial cells. Cytotoxicity and phytotoxicity were determined by brine shrimp lethality and Lemna minor bioassay. Caco-2 (colorectal adenocarcinoma) cell line was used for the evaluation of the anticancer effects. Result: Among the fractions tested, ethyl acetate (EA) fraction was found to be active with minimum inhibitory concentration (MIC) of 750 μg/mL against E. faecalis, but other fractions were found to be insensitive to bacterial growth. Microscopically, the EA fraction-treated bacteria showed highly damaged cells with their cytoplasmic content scattered all over. The LC50 value of the EA fraction against brine shrimp was more than 1000 μg/mL showing the nontoxic nature of this fraction. Chloroform (CH), EA, and methanol (MOH) fractions of C. excavata were highly herbicidal at the concentration of 1000 μg/mL. EA inhibited Caco-2 cell line with an IC50 of 20 μg/mL. Conclusions: This study is the first to reveal anti-E. faecalis property of EA fraction of C. excavata leaves, natural herbicidal, and anticancer agents thus highlight the potential compound present in its leaf which needs to be isolated and tested against multidrug-resistant E. faecalis.